2013
DOI: 10.1007/s15010-013-0546-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of universal influenza vaccines based on influenza virus M and NP genes

Abstract: The matrix protein (M1, M2) and nucleoprotein (NP) of influenza viruses have highly conserved sequences, and they become the major target antigens of current UIV studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 70 publications
1
48
0
Order By: Relevance
“…Previous studies have shown that NP-and M1-based immunization protect mice against lethal challenge with influenza virus (Boyd et al, 2012;Donnelly et al, 1997;Zheng et al, 2013). However, most reported NP-and M1-based vaccines are DNA- (Antrobus et al, 2014;Donnelly et al, 1997;Ohba et al, 2007;Zhirnov et al, 2007) or viral-skeleton-based (Antrobus et al, 2012;Choi et al, 2012;Lillie et al, 2012;Price et al, 2010;Quan et al, 2012), and other papers indicated that NP-based vaccines fail to provide complete protection against influenza virus (Chen et al, 1998;Jamali et al, 2010;Krammer and Palese, 2014;Lawson et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NP-and M1-based immunization protect mice against lethal challenge with influenza virus (Boyd et al, 2012;Donnelly et al, 1997;Zheng et al, 2013). However, most reported NP-and M1-based vaccines are DNA- (Antrobus et al, 2014;Donnelly et al, 1997;Ohba et al, 2007;Zhirnov et al, 2007) or viral-skeleton-based (Antrobus et al, 2012;Choi et al, 2012;Lillie et al, 2012;Price et al, 2010;Quan et al, 2012), and other papers indicated that NP-based vaccines fail to provide complete protection against influenza virus (Chen et al, 1998;Jamali et al, 2010;Krammer and Palese, 2014;Lawson et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These can be delivered as protein, peptide-carrier conjugate, VLP, DNA plasmid or by viral vectors [68]. However, also other relatively conserved influenza virus proteins might be considered for the induction of cross-reactive T cell responses, like the polymerase subunits (PA, PB1 and PB2).…”
Section: Targets For Influenza Vaccine Developmentmentioning
confidence: 99%
“…Moreover, recombinant protein vaccines have excellent safety, and can induce adequate antibody levels in a population vaccination, and therefore have become an important direction of influenza vaccine development at present. 9 However, if a new pandemic influenza virus breaks out, vaccination with a recombinant protein vaccine seems to be insufficient. Therefore, to further improve effectiveness of UIV, researchers tried to achieve the desired goals through combined use of multiple target antigens.…”
Section: Introductionmentioning
confidence: 99%